Characterisation of Streptococcus suis Isolates in the Czech Republic Collected from Diseased Pigs in the Years 2018-2022 - Zouharová, Monika; Šimek, Bronislav; Gebauer, Jan; Králová, Natálie; Kucharovičová, Ivana; Plodková, Hana; Pecka, Tomáš; Brychta, Marek; Švejdová, Marie; Nedbalcová, Kateřina; Matiašková, Katarína; Matiašovic, Ján (Pathogens (Basel, Switzerland), 2022)
As in other countries, in the Czech Republic, Streptococcus suis infection in pigs is considered an economically significant disease for the pig industry, though little is known about its population structure. We collected S. suis isolates from 144 farms in the years 2018-2022. All samples were taken from animals suffering from symptoms indicating possible S. suis infection. Serotyping revealed the presence of 23 different serotypes, and 18.94% were non-typable strains. The most common was S7 (14.96%), while other serotypes had frequencies of less than 10%. Sequence typing identified 56 different sequence types, including 31 newly assigned sequence types together with 41 new alleles in genes in the MLST schema. A large portion of isolates (25.70%) were of unknown sequence type. The most common sequence types were ST29 (14.77%) and ST28 (10.04%); the other sequence types had frequencies of less than 10%. In total, 100 different combinations of serotypes and sequence types were identified. Among them, S7ST29 was found in 72 isolates, representing 13.63% of all isolates, and was significantly associated with the central nervous system. Many other isolates of particular serotype and sequence type combinations were found in a few cases, and a number of isolates were non-typable.
Keywords: serotype; sequence type; pathotype; Streptococcus suis